A Comparison of The Learning Results Through the Design Thinking Process and Inquiry-Based learning (5E) to Scientific Competencies of Grade 8 Students - Butsai, Supaporn; Sakuntanak, Panida; Langka, Wilailak (Academic MCU Buriram Journal, 2023)
The purposes of this research were as follows: 1) to compare the scientific competencies of students who were taught by a design thinking approach before and after learning. 2) to compare the students' scientific competencies between the groups that performed the design thinking approach and those that performed the inquiry-based learning (5E). The samples of this research were grade 8 students at Surathampitak School, under the Office of Secondary Educational Service Area, Nakhon Ratchasima, semester 2, the academic year 2022; there are a total of 70 students divided into learning management through the design thinking of 35 students and inquiry-based learning (5E) 35 students. This study employed a two-stage random sampling. This research took four weeks to collect the data. The data was collected using a randomized control group pretest-posttest design and research tools consisting of a scientific competencies test, 4 Design thinking lesson plans, and 4 inquiry-based learning (5E) lesson plans. Analyzed by descriptive statistics, Mean (M), standard deviation (SD), skewness (Sk) and kurtosis (Ku), Hotelling’s T2, and MANOVA. The research results found that: 1. The students who were managed by the design thinking process had overall scientific competence. and classified by performance after learning was higher than before learning at statistical significance at the .05 level. 2. The students who received the design thinking learning management process had higher overall and classified scientific competencies after taking the approach than students who acted inquiry-based learning (5E) with statistical significance at the .05 level.